ЯРУУ НАЙРАГЧ ДАНЗАНГИЙН НЯМСҮРЭНГИЙН УРАН БҮТЭЭЛ ДЭХ ОРОН ЗАЙ, ЦАГ ХУГАЦААНЫ ДҮРСЛЭЛИЙГ АЖИГЛАВАЛ.. - Б.Пүрэв-Очир,; Л.Цэрэнчимэд, (Acta Mongolica, 2013)
It is observed that spatial and time descriptions by the poet can be explained in relation to "grass and nature or grass and human being”，Why is there "grass and snow”,“grass and rain", “grass and woman", “grass and love" or "grass and bird”？The poet's striking use ofmetaphor and interlext should be carefully explained by cognitive and comprehensible forms. Although the poet did not intend to portray space in a particular line or time in particular phrases or spatial and time interconnections in a verse, interestingly, spatial and time descriptions in his poems are revealed in the following ways: time and spatial description lines are intersected in a verse of poems or time and spatial description is described in one of the words in a sentence line. We have watered roots of some *grass* by D.Nyamsuren, the poet and teacher of Mongolian language and literature. Hope it will help it grow bigger!